Karl Barth and the analogia entis - Johnson, Keith L. (T & T Clark studies in systematic theology ;, 2010)
Many interpreters argue that Karl Barth's rejection of the Roman Catholic analogia entis was based upon a mistaken interpretation of the principle, and many scholars also contend that late in his career, Barth changed his mind about the analogia entis, either by withdrawing his rejection of it or by adopting some form of it as his own. This book challenges both views, and by doing so, it opens up new avenues for ecumenical dialogue between Protestants and Roman Catholics. In short, this book establishes that Barth did not make a mistake when he rejected the analogia entis and that he also neve.